1987
DOI: 10.1128/mcb.7.7.2425
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rat albumin promoter tissue specificity analyzed by an improved transient expression system.

Abstract: The 150-base-pairs region located upstream of the transcriptional start site of the rat albumin gene contains all of the critical sequences necessary for this gene's tissue-specific expression in rat hepatoma cells. In transient expression assays using an improved CAT system or direct mRNA analysis we were able to detect a faithful transcription from the albumin promoter in albumin-negative dedifferentiated H5 hepatoma cells which was 250-fold weaker than in differentiated H411 hepatoma cells producing albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
103
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 36 publications
4
103
0
1
Order By: Relevance
“…The start of transcription and numbering of upstream sequences were according to Malgaretti et al [22]. The chloramphenicol acetyltransferase reporter gene (CAT) plasmid pKT has been described [23]; to this plasmid, mouse MOS oncogene sequences were inserted in the SacI site of the polylinker creating plasmid pCAT-MOS [24]. The latter is the basic plasmid to which plasminogen genomic fragments were added.…”
Section: Methodsmentioning
confidence: 99%
“…The start of transcription and numbering of upstream sequences were according to Malgaretti et al [22]. The chloramphenicol acetyltransferase reporter gene (CAT) plasmid pKT has been described [23]; to this plasmid, mouse MOS oncogene sequences were inserted in the SacI site of the polylinker creating plasmid pCAT-MOS [24]. The latter is the basic plasmid to which plasminogen genomic fragments were added.…”
Section: Methodsmentioning
confidence: 99%
“…Rat hepatoma H4II cells and the dedifferentiated derivative H5 cells were grown and transfected, and enzymatic assays were performed, as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…Third, additional sequences sometimes prove to be required in order to obtain the correct expression pattern in transgenic mice (18). This is the case for the albumin gene (31): in transgenic mice, abundant and liver-specific albumin gene transcription requires the presence of a region located between -8.5 and -10.4 kilobases in addition to the promoter.We have previously shown that the 150 base pairs upstream of the rat albumin gene constitutes a fully functional promoter in the differentiated hepatoma cell line H4II (32), where it is as active as the sinian virus 40 early promoter (20). In striking contrast, in dedifferentiated H5 hepatoma cells (12) or in fibroblasts, this promoter is 100-fold less active.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We and others have attempted to identify and delete the respective prokaryotic sequences (SchOle et al, 1988) giving rise to high background of cat expression in some cell lines. Also, insertion of 'terminator' sequences has been suggested to prevent initiation of cat transcripts at cryptic promoters in the vector (Heard et al, 1987). To improve pBLCAT2 and pBLCAT3, we have combined both strategies: 467 bp of vector sequence immediately upstream from the polylinker were deleted and replaced by two fragments, each containing the polyadenylation signal of the SV40 large T encoding gene.…”
mentioning
confidence: 99%